2004
DOI: 10.1164/rccm.200308-1071oc
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cytokine Gene Expression in the Diaphragm in Response to Strenuous Resistive Breathing

Abstract: Strenuous resistive breathing induces plasma cytokines that do not originate from circulating monocytes. We hypothesized that cytokine production is induced inside the diaphragm in response to resistive loading. Anesthetized, tracheostomized, spontaneously breathing Sprague-Dawley rats were subjected to 1, 3, or 6 hours of inspiratory resistive loading, corresponding to 45-50% of the maximum inspiratory pressure. Unloaded sham-operated rats breathing spontaneously served as control animals. The diaphragm and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
97
0
14

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(121 citation statements)
references
References 75 publications
10
97
0
14
Order By: Relevance
“…There were previously reported that OVA increased the breathing resistance of the mice [11], resistive breathing induced IL-4 expression in diaphragm muscle [12], Th2 cytokines such as IL-4 and IL-13 induce iNOS expression through the STAT-6 pathway [13][14][15][16][17], iNOS reduced diaphragm muscle contraction, inhibition of iNOS induction and inhibition of NOS activity prevented diaphragm muscle contractile dysfunction [18]. Study results of ours are in agreement with study that previously reported.…”
Section: Discussionsupporting
confidence: 93%
“…There were previously reported that OVA increased the breathing resistance of the mice [11], resistive breathing induced IL-4 expression in diaphragm muscle [12], Th2 cytokines such as IL-4 and IL-13 induce iNOS expression through the STAT-6 pathway [13][14][15][16][17], iNOS reduced diaphragm muscle contraction, inhibition of iNOS induction and inhibition of NOS activity prevented diaphragm muscle contractile dysfunction [18]. Study results of ours are in agreement with study that previously reported.…”
Section: Discussionsupporting
confidence: 93%
“…The elevation in neutrophils and macrophages in the diaphragm in the present study is consistent with other observations after lengthening contractions of muscle [47,48], electrically stimulated contractions [49] and exposure of muscle to toxin or poison [41,42], but contrary to other recent reports [50,51]. Of these two differing reports, one described the extensor digitorum longus (EDL) muscle in response to in situ lengthening contractions [50] and the other investigated the diaphragm in response to resistive loading [51].…”
Section: Load-induced Diaphragm Inflammationsupporting
confidence: 91%
“…This view is based on the observations that strenuous resistive breathing and whole body exercise in healthy humans, such as treadmill running, induce signifi cant elevations of plasma pro-infl ammatory cytokine levels, including IL6, IL-1β, and TNFα and that this production is mediated in part by increased oxygen radical production (Vassilakopoulos et al 1999(Vassilakopoulos et al , 2002Ostrowski et al 1998). This role of ventilatory muscles as a source of systemic infl ammation has been confi rmed in an animal model of inspiratory resistive loading, where increased work of breathing signifi cantly upregulates IL6, IL1β and TNFα expressions within the diaphragm (Vassilakopoulos et al 2004). A recent study by Casadevall and colleagues (2007) has confi rmed that TNFα and IL6 levels are signifi cantly elevated in the intercostal muscles of COPD patients.…”
Section: Infl Ammationmentioning
confidence: 93%